Controllable nanoporous fibril-like morphology by layer-by- layer self-assembled films of bioelectronics poly(pyrrole-co-formyl pyrrole)/polystyrene sulfonate for biocompatible electrode. (March 2018) - Pattananuwat, Prasit; Tagaya, Motohiro; Kobayashi, Takaomi
Graphical abstract: Highlights: Controllable highly degree of nano porous/fibril-like network of P (Py- co -FPy) morphology on top surface film by LBL technique. Modulation of morphology, charge, conductivity and wettability of film for bioaffinity surface by LBL technique. Fibril-like structure of P(Py- co -FPy)/PSS layers can influences the BSA and Fgn absorption. P(Py- co -FPy)/PSS LBL electrode completely reveals non-cytotoxicity. Abstract: We demonstrate a new class of nanocoating materials for biocompatible electrode based on poly (pyrrole- co -formyl pyrrole) (P(Py- co -Fpy)) multilayered with polystyrene sulfonate (PSS) using layer by layer (LBL) self-assembly technique. By modulating the number layer of deposition, the unique surface properties of P(Py- co -Fpy) are evaluated for bioaffinity. Atomic force microscopy (AFM) demonstrates the controllable morphology of the degree fibril network structure of P(Py- co -Fpy)/PSS surface. The direct adsorption of bovine serum albumin (BSA) onto the top surface of P(Py- co -Fpy)/PSS film by AFM analysis reveals the forming of BSA multilayer at high degree of fibril structure P(Py- co -Fpy). In addition, the adsorbed fibrinogen (Fgn) reveals the reversible conformation change on surface of P(Py- co -Fpy)/PSS. The effect of P(Py- co -Fpy)/PSS morphology on primary mouse embryonic fibroblasts (MEF) is investigated. Cell morphology and proliferation on P(Py- co -Fpy)/PSS LBL film at different number of layer deposition are evaluated, demonstrating that P(Py- co -Fpy)/PSS LBL nanocoating surface is non-cytotoxic as morphology-dependent.